American contagions : epidemics and the law from smallpox to COVID-19 - Witt, John Fabian (Business book summary, 2020)
"From yellow fever to smallpox to polio to AIDS to COVID-19, epidemics have prompted Americans to make choices and answer questions about their basic values and their laws. In five concise chapters, historian John Fabian Witt traces the legal history of epidemics, showing how infectious disease has both shaped, and been shaped by, the law. Arguing that throughout American history legal approaches to public health have been liberal for some communities and authoritarian for others, Witt shows us how history's answers to the major questions brought up by previous epidemics help shape our answers today: What is the relationship between individual liberty and the common good? What is the role of the federal government, and what is the role of the states? Will long-standing traditions of government and law give way to the social imperatives of an epidemic? Will we let the inequities of our mixed tradition continue?"--Amazon